Optically and electrically invariant multi-color single InGaN/GaN nanowire light-emitting diodes on a silicon substrate under mechanical compression. Issue 12 (9th March 2023) - Qu, Juntian; Wang, Renjie; Pan, Peng; Du, Linghao; Sun, Yu; Liu, Xinyu
Abstract : Opto-electro-mechanical characterization of single InGaN/GaN nanowire light-emitting diodes (LEDs) reveals no significant effect of mechanical stress on the LED performance. Abstract : Recent years have seen immense advances in electroluminescent InGaN-based light-emitting diodes (LEDs) that may revolutionize lighting and display technologies. Driven by the need for the development of submicrometer-sized, multicolor light sources monolithically integrated on a single chip, it is necessary to accurately characterize the size-dependent electroluminescence (EL) properties of selective-area grown single InGaN-based nanowire (NW) LEDs. Moreover, InGaN-based planar LEDs generally undergo; external mechanical compression induced by the packaging process which could potentially degrade the emission efficiency this further motivates us to investigate the size-dependent EL properties of single InGaN-based NW LEDs on a Si substrate under external mechanical compression. In this work, we perform opto-electro-mechanical characterization of single InGaN/GaN NWs using a scanning electron microscopy (SEM)-based multi-physical characterization technique. We first tested the size-dependent EL properties of selective-area grown single InGaN/GaN NWs on a Si substrate with a high injection current density up to 12.99 kA cm −2 . In addition, the effect of external mechanical compression on the EL properties of the single NWs was investigated. Stable EL properties (no degradation of EL peak intensity and no peak wavelength shift) and electrical characteristics have been observed by applying a 5 μN compressive force to single NWs with different diameters. The results confirm no degradation of the NW light output with the applied stress (up to 62.2 MPa) and demonstrate the superior optical and electrical robustness of single InGaN/GaN NW LEDs under mechanical compression.